Compact and Large‐Area Perovskite Films Achieved via Soft‐Pressing and Multi‐Functional Polymerizable Binder for Flat‐Panel X‐Ray Imager. (5th January 2022) - Xia, Mengling; Song, Zihao; Wu, Haodi; Du, Xinyuan; He, Xin; Pang, Jincong; Luo, Hongde; Jin, Libo; Li, Guifeng; Niu, Guangda; Tang, Jiang
Abstract: Thanks to its strong X‐ray absorption and large carrier diffusion length, perovskites have demonstrated excellent performance for X‐ray detection. Combination of perovskite with thin‐film transistor (TFT) arrays to construct flat‐panel X‐ray imager (FPXI) is required for X‐ray imaging, yet this is rarely reported. Solution processing of perovskite thick film onto TFT can enable the electronic connection, however the amounts of pinholes inevitably form during the solvent evaporation and result in a porous film with deteriorated performance and stability. Here a novel strategy is raised to achieve high‐quality perovskite thick films for TFT integration via soft‐pressing and in situ polymerization of multi‐functional binder (TMTA). The combined process largely eliminates the pinholes, improves the surface smoothness, passivates grains boundaries, reduces ionic migration, and improves stability. Accordingly, a compact and smooth MAPbI3 thick film integrating with TFT arrays is prepared for flat‐panel X‐ray imaging. The largest film (28 × 28 cm 2 ) is obtained with the state‐of‐the‐art performance (ratio of sensitivity to noise current: 1.41 × 10 11 µC Gy −1 A −1 ) among polycrystalline films. It is hoped that the work provides guidance for fabricating compact perovskite thick films and push perovskite FPXI one step further for low‐dose X‐ray imaging. Abstract : By combining soft‐pressing and a multi‐functional polymerizable binder (TMTA), MAPbI3 thick film (≈400 µm) with compact structure, smooth surface, passivated grain boundaries, large area, high uniformity, and state‐of‐the‐art detection performance is achieved. The high‐quality perovskite thick film is successfully integrated with back‐end thin‐film transistor arrays and excellent large‐area X‐ray imaging is read out.